Hubungan Loan to Deposit Ratio (LDR) dan Return on Asset (ROA) - Sri Winarsih Ramadana (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2022)
This study aimed to determine the effect of the Loan Deposit Ratio on Return on Assets in banking companies listed on the Indonesia Stock Exchange in 2017-2020. The data analysis method in this study uses simple linear regression to predict the effect of the independent variables. The population in this study is all banks listed on the Indonesian Stock Exchange from 2017-2020, namely 42 banks. Furthermore, 30 samples were obtained. Of all the research samples, there were 30 banks with 120 research observations, namely 30 banks multiplied by the four years of the research period. The sampling method in this study was the purposive sampling method. The study results show that the Loan Deposit Ratio (LDR) significantly negatively affectsReturn on Assets (ROA). Overall, it shows that the higher the LDR, the lower the ROA. That is if the bank provides more loans than the ammo number funds collected from customer deposits, the profit generated by the bank (ROA) will be lower.